Efficiency evaluation of service marketing at a Hungarian telecommunication company - Kalmár, Katalin; Kárpáti, László (Acta Agraria Debreceniensis, 2009)
The article discusses the marketing effectivity of a communication service at a Hungarian telecommunication company. The main target is to establish economic effectivity of the enchanced promotion of the service. The basic metholodogy was the comparison of a new marketing plan and real figures of the planned period. The results of 2005 and 2006 show a verypositive financial effectivity of the surplus communication. Based on the results a further promotion is suggested.